Quantitative Analysis of Indian Mutual Funds: Equity Schemes - Prakash, S.; Sundar, C. (Indian Journal of Finance, 2014)
Mutual funds are an integral part of the stock market, which have become an investment avenue for a large number of investors in recent years. There are a number of investment opportunities available to an investor. Each of these investments has its own risk and return features. The present study was conducted to evaluate and compare the performance of equity mutual fund schemes of selected companies (HDFC, ICICI, and Franklin Templeton).